2011
DOI: 10.1080/02560046.2011.552211
|View full text |Cite
|
Sign up to set email alerts
|

Becoming global, remaining local: the discourses of international news reporting by CCTV-4 and Phoenix TV Hong Kong

Abstract: In an attempt to examine the issue of glocalisation in contemporary Chinese media practice, the article develops a tripartite framework which examines the discourses of global/Western vs. local/Eastern interactions in news reporting along three dimensions: the nature of the news event reported, the stance adopted in reporting the news, and the move structure involved in the reporting. The projection and discursive management of the international news reports by two prominent broadcast media channels in Cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
(10 reference statements)
1
16
0
Order By: Relevance
“…If it is representative of a class of titles, however, it is evidence that the strategies that have been used to popularise and legitimise the contemporary form of the Communist Party's rule in, for example, television drama, have a parallel in the newspaper press. In that context, the case of Phoenix TV's news programmes, which replicate more or less the same agenda on important issues as Xinwen Lianbo, while presenting these topics using techniques familiar from CNN or the BBC, suggests itself as a close parallel (Wu & Ng, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…If it is representative of a class of titles, however, it is evidence that the strategies that have been used to popularise and legitimise the contemporary form of the Communist Party's rule in, for example, television drama, have a parallel in the newspaper press. In that context, the case of Phoenix TV's news programmes, which replicate more or less the same agenda on important issues as Xinwen Lianbo, while presenting these topics using techniques familiar from CNN or the BBC, suggests itself as a close parallel (Wu & Ng, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In spheres of communication less subject to globalization, such as institutional meetings and family gatherings, cultural influence on language seems to be stronger and to have a longer-lasting and more durable effect on how entities are perceived. Wu and Ng (2011) take a similar position concerning journalistic practices in mainland China and Hong Kong. They argue that globalization has had only marginal effects, such as increasing the use of the dialogic story-telling structure, with Chinese values, such as the need for harmony, remaining intact as the normative view of journalism.…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%
“…These values are tied with Chinese foreign correspondents' roles, domestic situations, and professionalization. Wu and Ng (2011) revealed that the Chinese broadcasters no longer avoided news of a negative nature but still a larger percentage of the news events reported by CCTV-4 was positive rather than negative. They argue that Chinese journalists, as the government's nation-building partners, use a harmony-oriented, supportive editorial stance in managing international news to project an image of a peace loving nation (ibid).…”
Section: Practicesmentioning
confidence: 99%
“…The Chinese media have undergone transformations from being a state propagandistic vehicle only to also "serving the interests of the global as well as the local audiences"; and from a state-owned media institution to "a media of capitalistic body with socialist characteristics". (Wu & Ng, 2011) In terms of ideology and values, Pan (2000) states that the center of China's party-press system is constituted by the "central value system" of communist ideology and the apparatus that enforces it. After the reform and opening up policy was established in the late 1970s, the Chinese government continued to immerse itself in the ideology of the Cold War, even after the collapse of the Soviet Union (Zhang 2012).…”
Section: Culturesmentioning
confidence: 99%